Evaluating Medication Adherence in Type-2 Diabetes: A Study of Drug Therapy Using the Medication Adherence Report Scale (MARS). - Kauser, Rubeena; Puligilla, Shankaraiah (Journal of Neonatal Surgery, 2025)
Objective: This study sought to evaluate the medication adherence and improvements in the diabetic patients using different combination therapies. Materials and method: This cross-sectional study included 193 T2D patients aged 18-80 years, receiving treatment for at least six months. The Medication Adherence Rating Scale (MARS) was used to assess medication adherence. Multiple regression and descriptive statistics were used to evaluate the data and find adherence predictors. Results: According to the statistics, dual therapy showed the greatest improvement in medication adherence, followed by triple therapy. The single therapy showed the least improvement in medication adherence, at 25%. There is a better adherence score for both triple therapy and dual therapy, as the research shows that the mean difference for triple therapy is the biggest, followed by dual therapy. Conclusion: The differing effectiveness of therapy approaches suggests that both physiological and behavioral outcomes should be considered when choosing a treatment to optimize patient care. The study's findings support the application of patient-centered, multifaceted diabetic treatment approaches that consider the complex interplay between clinical efficacy and adherence behaviors.